НОРАВШАН ТЕНГЛАМАЛАР ТИЗИМИНИНГ КОМПАКТ ЕЧИМИНИ ТОПИШ - Мухамедиева, Д.Т. (SCIENCE and SOCIETY, 2023)
This article explores finding fuzzy solutions to linear equations and their compactness, examining methods and conditions for practical applications. It offers theoretical analysis and experimental results, benefiting researchers and practitioners in fuzzy logic, optimization, and decision-making.
Keywords: primary information; compactness; fuzzy set; relevance function; space